2021
DOI: 10.1590/1516-4446-2020-0904
|View full text |Cite
|
Sign up to set email alerts
|

Association between exposure to toxoplasmosis and major psychiatric disorders: a systematic review

Abstract: Objective: To assess the association between exposure to toxoplasmosis and major psychiatric disorders through a systematic review of the literature. Methods: The literature review was performed in the MEDLINE, SciELO, and PsycINFO databases. To evaluate the quality of the studies included in the review, the Newcastle-Ottawa Scale was used. Results: Thirty-one studies were included, and the majority found an association between exposure to toxoplasmosis and schizophrenia or bipolar disorder (58.3 and 54.5% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(104 reference statements)
0
0
0
Order By: Relevance
“…Also, Liu et al (2022) recorded a high seroprevalence of T. gondii infection in psychiatric patients and that age was an influencing factor. But, Fernandes et al (2020) reported that MDD didn't associate with anti-T. gondii IgG and IgM. The depressed patients had a lower seroprevalence of T. gondii as compared to controls, and they concluded that toxoplasmosis is not a risk factor for depression.…”
Section: Introductionmentioning
confidence: 98%
“…Also, Liu et al (2022) recorded a high seroprevalence of T. gondii infection in psychiatric patients and that age was an influencing factor. But, Fernandes et al (2020) reported that MDD didn't associate with anti-T. gondii IgG and IgM. The depressed patients had a lower seroprevalence of T. gondii as compared to controls, and they concluded that toxoplasmosis is not a risk factor for depression.…”
Section: Introductionmentioning
confidence: 98%